The The Effect of Adding Clonidine to Articaine and Epinephrine on Post-treatment Pain: A Randomized Clinical Trial Study - Shadmehr, Elham; Hashemi, Sara; Hashemi, Seyed Saman; chung, Yoo jung; Goudarzi, Arman; Khademi, Abbasali (Iranian Endodontic Journal, 2021)
Introduction: Articaine is reported to have a fast onset and a short-acting pulpal anesthesia in inferior alveolar nerve blocks. Clonidine is an α2-adrenoceptor agonist and is used as an adjunct to enhance the anesthetic efficacy and induce greater analgesia. In an attempt to search for more effective ways to achieve profound analgesia after root canal treatment, this randomized clinical trial assessed the efficacy of clonidine added to articaine/epinephrine solution on post-operative pain relief after root canal treatment in mandibular molars with irreversible pulpitis. Materials and Methods: Our randomized clinical trial study enrolled one hundred patients with symptomatic irreversible pulpitis in mandibular molars. They were divided into two groups, each group received either 0.2 mL 150 µg/mL clonidine or distilled water added to 1.8 mL of 4% articaine with 1:100,000 epinephrine cartridge. The alveolar nerve block in the two groups was administered by the same clinician and the subject’s pain scores were recorded at 6, 12, 24, 48 and 72 h post-operatively using a Heft-Parker visual analog scale. Data were analyzed using t, chi-square and repeated-measures ANOVA statistical tests. Results: The mean pain scores for clonidine group were significantly lower than control at all the time intervals after treatment (P<0.05). We did not notice any clinical and there were no complaints from the patients either. Conclusion: Based on this randomized clinical trial study the addition of clonidine to the articaine/epinephrine solution using an inferior alveolar nerve block during root canal treatment in mandibular molars with irreversible pulpitis may be effective in reducing post-operative pain.